Metamaterial Layer Loaded on Log Periodic Antenna for Energy Harvesting - Levy Olivia Nur; Quzwain, Kamelia; Wahid Nur Hamid; Aisyah Novfitri; Mudrik Alaydrus (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2026)
This paper investigates metamaterial layer loaded on a log periodic antenna for Radio Frequency (RF) energy harvesting. The proposed antenna was designed at a frequency of 5.8 GHz using Rogers RT5880 substrate with a thickness of 0.787 mm. The log periodic antenna covered with a metamaterial layer was simulated and analyzed. The computational results show a good agreement in which the proposed antenna is able to produce -13.5 dB return loss and 8.3 dB gain with a compact size of 40 x 50. It implies that the proposed concept in this paper can be implemented to increase the antenna performance.